2015
DOI: 10.1007/s11120-015-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyanofuels: biofuels from cyanobacteria. Reality and perspectives

Abstract: Cyanobacteria are represented by a diverse group of microorganisms that, by virtue of being a part of marine and freshwater phytoplankton, significantly contribute to the fixation of atmospheric carbon via photosynthesis. It is assumed that ancient cyanobacteria participated in the formation of earth's oil deposits. Biomass of modern cyanobacteria may be converted into bio-oil by pyrolysis. Modern cyanobacteria grow fast; they do not compete for agricultural lands and resources; they efficiently convert excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 87 publications
2
59
0
3
Order By: Relevance
“…Therefore, it could be concluded that this scheme is unproductive for light energy bioconversion due to the numerous intermediate steps. Alternatively, direct light-dependent production of biofuels (ethanol, lipids, or hydrogen) by microalgae as elaborated by Sarsekeyeva et al (2015) and Tsygankov and Abdullatypov (2015) might be more profitable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be concluded that this scheme is unproductive for light energy bioconversion due to the numerous intermediate steps. Alternatively, direct light-dependent production of biofuels (ethanol, lipids, or hydrogen) by microalgae as elaborated by Sarsekeyeva et al (2015) and Tsygankov and Abdullatypov (2015) might be more profitable.…”
Section: Discussionmentioning
confidence: 99%
“…Among various beneficial microbes, cyanobacteria can be used in nutrition, energy and agriculture sector because of their ability to fix atmospheric N 2 and CO 2 , and produce energy rich biomass containing myriad of metabolites of economic importance. Furthermore, recent developments in cyanobacterial screening, cultivation, and gene manipulation techniques have enabled new ways to utilize the potential of these photosynthetic microbes to deal with socio-economic problems (Sarsekeyeva et al, 2015).…”
Section: Sustainable Agriculture and Microbesmentioning
confidence: 99%
“…Therefore, generation of microbiological energy through massive solar energy transformation permits harvesting various forms of eco-friendly energy reserves (Hall et al, 1995;Paumann et al, 2005). The aforementioned characteristics make cyanobacteria potential microorganisms for their application as feedstocks for sustainable production of food and non-food commodities, including valuable chemicals and bioenergy (Wase and Wright, 2008;Sarsekeyeva et al, 2015;Rajneesh et al, 2017). Cyanobacteria produce a number of valuable compounds such as ethanol, butanol, fatty acids, and other organic acids, and therefore, are promising candidates for fulfilling our energy demands in a sustainable manner .…”
Section: Introductionmentioning
confidence: 99%
“…The production of biofuel from cyanobacteria has several advantages [discussed by Quintana et al (2011) and Sarsekeyeva et al (2015)]. Among these advantages is the fact that many cyanobacteria, e.g., Spirulina and Synechococcus, accumulate high amounts of glycogen, which can be easily extracted and fermented to ethanol (See Conversion of Glycogen to Glucose).…”
Section: Cyanobacteria Serve As a Minor Source For Third-generation Bmentioning
confidence: 99%